Formation Mechanism and Prediction Method for the Permian Fused Breccia Tuff Reservoir, Wuxia Region, Junggar Basin. (23rd June 2021) - Xu, Duonian; Pan, Jianguo; Pan, Shuxin; Gao, Bin; Yin, Lu; Qu, Yongqiang; Zhang, Lei
Abstract : Fused breccia tuff occurs globally, but its formation mechanism is very controversial. Volcanic reservoirs have developed at the bottom of the Permian Fengcheng Formation in the Wuxia region of the Junggar Basin, and here, the lithology is fused breccia tuff. The reservoir porosity is mainly vesicles, but the development and relative filling of the vesicles vary spatially, resulting in strong reservoir heterogeneity. Through core and thin section observations and structural analysis, and combined with reconstructions of the paleosedimentary environment, we discussed in detail the formation mechanism of the fused breccia tuff reservoir. Our conclusions are as follows. In the high-temperature and high-pressure environment of the deep crust, intermediate acidic lava containing volatile components rapidly rose to the earth's surface along a fault. The volatile components in the lava foamed strongly and then exploded due to the sharp decline of pressure and temperature. A small part of the volcanic dust and pyroclastic material was erupted into the upper atmosphere. Most of the magma became magmatic pyroclast, vitric pyroclast, rock debris, dust, and other matter. This material was in a semimolten state and overflowed into a nearby low-lying lake. The extremely high-temperature pyroclastic flow quickly vaporized the water into high-pressure water vapor, which was squeezed into the pyroclastic flow and became mixed with other volatiles in the foam. On cooling, the pyroclastic material solidified into rock, and the vesicles were preserved. In a later period, due to strong tectonic movement, faults and fractures developed, surface water penetrated into the vesicles along the faults and fractures, and silica and other substances were deposited, filling the primary vesicles. To quantify the development and relative filling of vesicles, drilling parameters were used to establish different geologic models, and wave equation forward modeling was used to obtain a relationship between the development and filling of vesicles, and the seismic amplitude. The 3D seismic amplitude attributes were then extracted to predict the extent of the reservoir, yielding prediction results consistent with the drilling observations.